PENGARUH KUALITAS PRODUK, CITRA MEREK, DAN MATERIALISME TERHADAP LOYALITAS MEREK PENGGUNA PRODUK APPLE DI KOTA DENPASAR - Cahyaning Dewi, Ni Nyoman Ayu Suri Tri; Suasana, I Gusti Agung Ketut Gede (E-Jurnal Manajemen; Vol 3 No 3 (2014), 2014)
This research was conducted in order to know the effect of product quality, brand image, brand loyalty and materialism against users of Apple products in the city of Denpasar. 160 respondents were sampled in the study by distributing questionnaires as data collection techniques. Multiple regression analysis is used as an analytical technique in the study. Findings provide results that there is a significant effect of product quality, brand image, and materialism simultaneously and partially on the brand loyalty of Apple product users in the city of Denpasar. Keywords: product quality, brand image, materialism, and brand loyalty